Faktor-faktor Yang Mempengaruhi Kemampuan UMKM dan Kesejahteraan UMKM Pada Koperasi Syariah Kaum Ibu Al-Ikhlas Medan - Indah Apriyani Nasution; Muhammad Yafiz; Nur Ahmadi Bi Rahmani (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to analyze the effect of financing, coaching, promotion, on the ability of micro-enterprises and increasing the welfare of micro-enterprises. The purpose of the cooperative is the welfare of its members and the programs provided by the cooperative to create new jobs for the community and members of the cooperative. This type of research uses quantitative research. The sample in this study are all members of sharia cooperatives who work at the Kaum Ibu Al-Ikhlas Sharia Cooperative in Medan City which are registered in the 2021 BPS, with a total of 152 members. Based on the results of the hypothesis analysis, it was obtained that P Values (0.00222) 1.96, it was concluded that Financing had a significant effect on Micro Enterprise Capability. Based on the analysis results obtained P Values (0.00111) < 0.05 and t statistics (3.28092) > 1.96.